2011
DOI: 10.1007/s00586-011-2104-z
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic intraoperative powdered vancomycin and postoperative deep spinal wound infection: 1,512 consecutive surgical cases over a 6-year period

Abstract: 15 of the 1,512 patients (0.99%) were identified as having evidence of postoperative deep wound infection. At least one pre-existing risk factor for deep infection was present in 8/15 pts (54%). Staphylococcus aureus and methicillin-resistant S. aureus (MRSA) were the most commonly identified organisms (11/15 cases). The rate of deep wound infection was 1.20% (8/663) for instrumented spinal surgeries, and 0.82% (7/849) for uninstrumented surgeries. Deep infection occurred in only 1.23% (4/324) of multilevel in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
144
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(164 citation statements)
references
References 31 publications
(50 reference statements)
4
144
1
6
Order By: Relevance
“…35 Literature such as that from the North American Spine Society has confronted topics such as patient education, nutritional status, and antibiotic prophylaxis, while other studies are surfacing on interwound antibiotic application, implants, and surgical approach benefits. 1,10,11,24,28,32,34 In 2012, the SRS began recording data regarding antibiotics, wound washout, and microorganisms. All data given as percentages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35 Literature such as that from the North American Spine Society has confronted topics such as patient education, nutritional status, and antibiotic prophylaxis, while other studies are surfacing on interwound antibiotic application, implants, and surgical approach benefits. 1,10,11,24,28,32,34 In 2012, the SRS began recording data regarding antibiotics, wound washout, and microorganisms. All data given as percentages.…”
Section: Discussionmentioning
confidence: 99%
“…There is great variation in the literature about bacterial speciation, but these are the main organisms consistently reported. 24,36,41 Continued insight into their prevalence can guide management principals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,6,7 Given the incidence of deep wound infections, several authors explored and subsequently published their results on locally applied prophylactic vancomycin antibiotic powder, in addition to systemic antibiotics, to reduce postoperative spinal SSIs. [2][3][4]9,[13][14][15][16][17][20][21][22]24 Perioperative vancomycin powder is an attractive option for additional prophylaxis against postoperative SSI due to its low cost and broad coverage. Numerous studies have shown that the addition of local vancomycin aBBreviatiONS BMI = body mass index; CDC = Centers for Disease Control and Prevention; COPD = chronic obstructive pulmonary disease; CTJ = cervicothoracic junction; EBL = estimated blood loss; MRSA = methicillin-resistant Staphylococcus aureus; SSI = surgical site infection.…”
mentioning
confidence: 99%
“…Numerous studies have shown that the addition of local vancomycin powder to standard systemic antibiotic prophylaxis reduced postoperative spinal SSI rates from 2.6%-15% to 0%-2.5%. 2,4,14,15,17,[20][21][22] A few cohort studies have looked at posterior cervical fusion cases and have reported significant reductions in the incidence of postoperative deep SSI rates from 10.9%-15.0% to 0%-2.5% after the introduction of perioperative vancomycin powder. 2,17,20 However, these studies were limited by small cohort patient sizes, with fewer than 172 total patients, and high control (nonvancomycin) postoperative SSI rates.…”
mentioning
confidence: 99%